IUS Constituendum Of Expert Advisor In Commodity Futures Trading: A Legal Certainty - Kurniawan, I Gede Agus; Mau Lulo, Lourenco de Deus; Disantara, Fradhana Putra (Magister of Law, Faculty of Law, University of Mataram, 2023)
This study aims to construct further arrangements regarding Expert Advisors in commodity futures trading. The legal issue being studied is the legal vacuum of regulating trading robot software or commonly known as an Expert Advisor in commodity futures trading. The novelty of this research is legal discovery through the legal construction of the development of Expert Advisors in commodity futures trading. The study confirmed that the urgency setting up an Expert Advisor as a futures adviser in commodity futures trading is needed in order to provide legal certainty for commodity futures transaction actors. Legal certainty related to the arrangement of Expert Advisors as futures advisers in commodity futures trading is also needed for CoFTRA as a supporting element of the Ministry of Trade as well as being a supervisor and enforcer of various legal provisions in the practice of commodity futures trading. Therefore, the supervision and enforcement process can be more optimal and guarantee legal certainty, benefits, and fairness for commodity futures trading actors. The Ius constituendum of expert advisor as an adviser in commodity futures trading to ensure legal certainty can be carried out by revising the Law on commodity futures trading, including conducting a judicial review at the Constitutional Court regarding the provisions in the Law on commodity futures trading.